2014
DOI: 10.1002/term.1864
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic fields promote osteogenesis of rat mesenchymal stem cells through the PKA and ERK1/2 pathways

Abstract: It has been reported that electromagnetic fields (EMFs) can promote the healing of non-union, osteogenesis and differentiation of the osteoblasts. However, its mechanism has not been unravelled. In this study, we detected some response induced by EMF and evaluated the importance of these signals for EMF-induced osteogenesis in bone marrow mesenchymal stem cells (MSCs). We characterized the expression of EMF-induced osteogenesis markers in MSCs, using RT-PCR and real-time PCR. Western blot was used to detect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…Ke et al found EMF exposure could cause the cluster- ing of epidermal growth factor (EGF) receptors and RAS activation (Ke et al, 2008). What is more, many researchers demonstrated that expression of phosphorylated ERK1/2 and P38 of BMSCs or osteoblasts could be promoted by EMF exposure, and the MAPK signaling pathway special inhibitor could inhibit the effect of EMFs on promoting osteogenic differentiation (Song et al, 2014a;Yong et al, 2014;Yuge et al, 2003). In conclusion, the RAS/RAF/MAPK signaling pathway may be another possible signaling pathway involving the biological effects of EMFs (Figure 1).…”
Section: Ras/raf/mapk Signaling Pathwaymentioning
confidence: 97%
“…Ke et al found EMF exposure could cause the cluster- ing of epidermal growth factor (EGF) receptors and RAS activation (Ke et al, 2008). What is more, many researchers demonstrated that expression of phosphorylated ERK1/2 and P38 of BMSCs or osteoblasts could be promoted by EMF exposure, and the MAPK signaling pathway special inhibitor could inhibit the effect of EMFs on promoting osteogenic differentiation (Song et al, 2014a;Yong et al, 2014;Yuge et al, 2003). In conclusion, the RAS/RAF/MAPK signaling pathway may be another possible signaling pathway involving the biological effects of EMFs (Figure 1).…”
Section: Ras/raf/mapk Signaling Pathwaymentioning
confidence: 97%
“…Hou et al (2006) indicated that EMF activated the extracellular signal-regulated kinase mitogen-activated protein kinase (ERK–MAPK) and p38 pathways [27]. In a study by Yong et al (2014), it was demonstrated that 15 Hz, 1 mT promoted mesenchymal stem cells (MSCs) osteogenesis and that the EMF-induced osteogenic markers were mediated by both the PKA and MAPK signaling pathways [28]. In fact, EMFs activate some of the signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the improvement of the present available technologies is still needed to acquire more satisfactory clinical outcomes in bone defect repair. PEMFs, as described above, have a marked function to accelerate the proliferation, osteogenic differentiation, and mutation of BMSCs by activating a series of signaling pathways [7, 21, 25, 31, 38, 73]. Moreover, the expressions of many osteogenesis- and angiogenesis-promoting cytokines, including TGF-β, BMPs, IGFs, FGFs, and VEGFs, in BMSCs are strikingly elevated by PEMF exposure.…”
Section: Therapeutic Applications Of Pemfs In Bone Repairmentioning
confidence: 99%
“…When the cells were treated with U0126, an inhibitor of the ERK1/2 signaling cascade, the positive effects of the ELF-PEMF treatment on osteoblast function were abolished [36]. Other studies also revealed that the MEK/ERK signaling pathway regulated the promoting effects of PEMF on bone marrow mesenchymal stem cell (BMSC) proliferation, expression of osteogenic genes (RUNX2, BSP, OPN), ALP activity, and calcium deposition [22, 32, 37, 38]. Additionally, one study reported that the p38 MAPK pathway is involved in the increased production of collagen synthesis in osteoblast-like cells stimulated by ELF-EMF exposure [39].…”
Section: Underlying Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation